Do facilitation payments affect earnings management? Evidence from China - Hu, Juncheng (Journal of Corporate Finance, 2021)
This study examines whether facilitation payments drive managers to manipulate earnings, thus weakening financial disclosure transparency. I find economically and statistically significant evidence that facilitation payments relate positively to earnings management levels in China. The impact of facilitation payments on earnings management is more pronounced when firms have relatively weak political power, less effective external monitoring, fewer growth options, and when firms are located in regions that have less efficient juridical systems. Finally, the findings are strengthened by a set of additional tests to mitigate the endogeneity problem: a difference-in-differences estimation that exploits China’s anti-corruption campaign as the exogenous shock, a dynamic analysis, an instrumental variable approach, and a Heckman analysis to adjust for selection bias. This study contributes to debates regarding corruption and transparency from a micro-economic perspective.